2017
DOI: 10.1186/s12985-017-0783-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative phosphoproteome on the silkworm (Bombyx mori) cells infected with baculovirus

Abstract: Background Bombyx mori has become an important model organism for many fundamental studies. Bombyx mori nucleopolyhedrovirus (BmNPV) is a significant pathogen to Bombyx mori, yet also an efficient vector for recombinant protein production. A previous study indicated that acetylation plays many vital roles in several cellular processes of Bombyx mori while global phosphorylation pattern upon BmNPV infection remains elusive.MethodEmploying tandem mass tag (TMT) labeling and phosphorylation affinity enrichment fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
4
6
0
Order By: Relevance
“…5B-5D). A similar GO enrichment pattern of differentially expressed host genes upon BmNPV infection in host cells (Shobahah et al 2017) as well as in Zika virus infected Aedes aegypti (Etebari et al 2017) had been reported. Maximum distribution of DEGs in the molecular functions category associated with binding activity had also been reported by Wang et al (2015) on the transcriptome of the brain of B. mori larvae infected with BmNPV, where its significance on mediating neuroactive steroids to activate membrane receptors had been discussed.…”
Section: Functional Annotations and Enrichment Analysissupporting
confidence: 71%
“…5B-5D). A similar GO enrichment pattern of differentially expressed host genes upon BmNPV infection in host cells (Shobahah et al 2017) as well as in Zika virus infected Aedes aegypti (Etebari et al 2017) had been reported. Maximum distribution of DEGs in the molecular functions category associated with binding activity had also been reported by Wang et al (2015) on the transcriptome of the brain of B. mori larvae infected with BmNPV, where its significance on mediating neuroactive steroids to activate membrane receptors had been discussed.…”
Section: Functional Annotations and Enrichment Analysissupporting
confidence: 71%
“…To analyze the density levels of the phosphorylation sites in each protein, the phosphorylated proteome of L. edodes was compared with those of other species. The average number of phosphorylation sites per protein in L. edodes is 3.22, which is similar to the numbers in Bombyx mori (3.07), Nicotiana tabacum (3.05), and Physcomitrella patens (3.44) ( Fig.2b) [34][35][36].…”
Section: Analysis Of Phosphorylation Sitessupporting
confidence: 66%
“…Protein phosphorylation is a universal PTM; however, the abundance of phosphorylation largely varies among different species. In C. moschata, the abundance of phosphorylated protein (2,853 phosphorylated proteins) was higher than most of the published species, such as Sus domesticus (966 phosphorylated proteins), Bombyx mori (2,112 phosphorylated proteins), Kandelia candel (1,516 phosphorylated proteins), Nicotiana tabacum (1,311 phosphorylated proteins), Lotus japonicus (1,154 phosphorylated proteins), Ammopiptanthus mongolicus (2,019 phosphorylated proteins), Catalpa fargesii (1,646 phosphorylated proteins), Abelmoschus esculentus (2,550 phosphorylated proteins), and Physcomitrella patens (1,873 phosphorylated proteins) 35,43,45,[50][51][52][53] . High-throughput method gives us an opportunity to screen potential phosphorylated proteins and reveal the involvement of protein phosphorylation in the responses to the C/NDRV infections.…”
Section: Discussionmentioning
confidence: 99%